Efektifitas LKPD IPAS untuk Meningkatkan Kemampuan Berpikir Kritis Siswa Sekolah Dasar - Wulansari, Shella Dyah Wulansari; Andini, Dea; Pramudiyanti, Pramudiyanti; Dewi, Pramita Sylvia (Lentera: Jurnal Ilmiah Kependidikan, 2024)
Critical thinking is a higher level thinking ability. In reality, students still have difficulty thinking critically when learning science. An effort is needed to improve critical thinking skills. The aim of this research is to determine the effectiveness of LKPD based on the Discovery Learning learning model in improving elementary school students' critical thinking skills. This type of research is quasi-experimental. This research involved 84 elementary school students in class V. The research sample consisted of 68 students. Data collection in this research was obtained from a learning outcomes test in the form of 12 essay questions. Data obtained was tested for normality and homogeneity and then analyzed using the t-test. In the experimental class the highest score was 85, the lowest score was 40, the average was 70.36, with a standard deviation of 9.36. In the control class the highest score was 48.7, the lowest score was 5, the average was 20.2, with a standard deviation of 8.94. In the process, students in the experimental class showed better critical thinking skills than control class students. From the results of this research it can be seen that the value of t_count = 41.12 > table = 1.668, so the hypothesis or H1 is accepted, thus the use of LKPD based on the Discovery Learning learning model has an effect on critical thinking skills in elementary school students.